(untitled) (Journal of Hama University, 2022)
the aim of this study is to evaluate the marginal bone loss (MBL) around zirconia implants that were used for the replace a missed single tooth. 12 locally manufactured zirconia implants (ISSA-NZI, one-piece implant) installed in the jawbones of patients who need to replace a missing posterior tooth, after two months for the mandible and four months for the maxilla, we crowned the abutments with zirconia crowns , and monitoring radiographs were taken after (1, 2, 3, 4, 6, 9, 12 and 14 months) of implantation. By this technique of x- ray photos, bone absorption peri- implants was evaluated, and averages of absorption values were recorded during the observation period The success rate of zirconia implants was 93%, the average of (MBL) after one year of rehabilitation was 1.03mm with (SD = ±0.05 mm) of the mesial side and 1.07 mm with (SD = ±0.07 mm) of the distal side The (MBL) of one-piece zirconia implants (ISSA-N.Z.I) is within clinically acceptable limits.